Fear of hypoglycaemia in patients with type 1 and 2 diabetes: a systematic review. Issue 1 (22nd November 2020) - Zhang, Yu; Li, Shuang; Zou, Yan; Wu, Xiaxin; Bi, Yaxin; Zhang, Lu; Yuan, Yuan; Gong, Weijuan; Hayter, Mark
Abstract: Aims and objectives: To summarise and thematise fear of hypoglycaemia (FOH) in individuals with type 1 diabetes (T1D) and type 2 diabetes (T2D) to provide a theoretical basis for the development of effective interventions. Background: FOH is common in this population and can reduce quality of life (QOL) and adversely impact upon diabetes self‐care management. Design: A systematic review. Methods: Articles published between 2000–2019 were searched in PubMed, MEDLINE, EMBASE, Web of Science and three Chinese databases (CNKI, Wan‐fang data and VIP). Eligible articles were selected using the Preferred Reporting Item for Systematic Review and Meta‐analysis (PRISMA) guidelines. The quality of all articles finally included was evaluated by the Joanna Briggs Institute (JBI) Critical Appraisal tools. Results: Eighteen studies from 8654 papers were included. The sample size of each study ranged from 48–3812 subjects. FOH negatively impacted QOL, particularly psychosocial functioning, daily life and sleep quality. Conclusions: FOH is a common and serious problem for patients, leading to poor QOL. It has been suggested that psychological concerns, QOL and effective countermeasures in individuals with T1D and T2D should be taken seriously. Advanced technology should be evaluated for its benefits before being used by patients. Relevance to Clinical Practice: The review highlights that FOH negatively impacts QOL, including psychosocial factors, daily life and sleep quality. Healthcare providers should develop targeted and professional assessment tools for FOH and QOL for patients with T2D, especially for patients who are about 60 years old. Advanced technology should be evaluated for its benefits before being used by patients.